Do refined consensus guidelines improve the uniformity of clinical target volume delineation for rectal cancer? Results of a national review project. Issue 2 (August 2016) - Joye, Ines; Macq, Gilles; Vaes, Evelien; Roels, Sarah; Lambrecht, Maarten; Pelgrims, Ans; Bussels, Barbara; Vancleef, An; Stellamans, Karin; Scalliet, Pierre; Weytjens, Reinhilde; Christian, Nicolas; et al.
Abstract: In a previous national central review project, 74% of the rectal cancer clinical target volumes (CTVs) needed a modification. In a follow-up initiative, we evaluated whether the use of refined international consensus guidelines improves the uniformity of CTV delineation in clinical practice.